2007
DOI: 10.1088/0957-4484/18/6/065702
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the luminescence of structures with Ge nanocrystals formed by dry and wet oxidation of SiGe films

Abstract: The luminescence emission of structures containing Ge nanocrystals embedded in a dielectric matrix obtained by dry and wet oxidation of polycrystalline SiGe layers has been studied as a function of the oxidation time and initial SiGe layer thickness. A clear relationship between the intensity of the luminescence, the structure of the sample, the formation of Ge nanocrystals and the oxidation process parameters that allows us to select the appropriate process conditions to get the most efficient emission has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…1(d), which shows the Raman signatures of the Ge/Si sample (top) and the pure Ge sample (bottom). In agreement with previous studies, 16,[21][22][23] the optical vibration modes observed after spectral deconvolution are assigned to the Ge-Ge chains containing Si impurities (peak 1, around 290 cm À1 ), pure Ge-Ge phonon (peak 2, around 295 cm À1 ), Ge-Si phonon (peak 3, around 400 cm À1 ), Si-Si phonon (peak 4, around 490 cm À1 ), and Ge-Ge two-phonon mode (peak 6, around 580 cm À1 ). The peak observed at 521 cm À1 (peak 5) corresponds to the TO phonon mode of the Si (001) substrate.…”
Section: Resultssupporting
confidence: 93%
“…1(d), which shows the Raman signatures of the Ge/Si sample (top) and the pure Ge sample (bottom). In agreement with previous studies, 16,[21][22][23] the optical vibration modes observed after spectral deconvolution are assigned to the Ge-Ge chains containing Si impurities (peak 1, around 290 cm À1 ), pure Ge-Ge phonon (peak 2, around 295 cm À1 ), Ge-Si phonon (peak 3, around 400 cm À1 ), Si-Si phonon (peak 4, around 490 cm À1 ), and Ge-Ge two-phonon mode (peak 6, around 580 cm À1 ). The peak observed at 521 cm À1 (peak 5) corresponds to the TO phonon mode of the Si (001) substrate.…”
Section: Resultssupporting
confidence: 93%
“…Instead, they were mostly related to the interface between Ge ncs and the SiO 2 matrix. Those two peaks at 3.19 eV and 4.40 eV have been observed by Skuja [32], Lopes [23], and Rodriguez [1], who attributed them to defects, formed by electrically neutral twofold-coordinated Ge atoms. These molecule-like luminescence centers have three-level energy emission in which blue-violet emission (3.19eV) and UV emission (4.40eV) are due to a triplet-to-singlet transmission and a singlet-to-singlet transition, respectively [23].…”
Section: Photoluminescencementioning
confidence: 60%
“…Zero-dimensional germanium (Ge) nanocrystals (ncs), also called nanoclusters or quantum dots, have undergone intensive theoretical and experimental research due to their potential applications as light emitters [1][2][3][4][5][6], non-volatile optical memories [7,8] and their enhanced third-order optical nonlinear effects [9][10][11][12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman bands, especially the Ge-Ge one, present a complex shape which reveals the existence of different contributions inside the scattering volume that can be attributed to differences between the NWs. The formation of crystalline Ge could be the consequence of the post-growth oxidation of the NWs, since the oxidation of SiGe is known to result in the formation of a Ge pileup layer beneath the silicon oxide [8,9]. These differences could be caused by the contribution of NWs with slightly different diameters to the Raman spectrum, since the diameter and the composition are known to be related [3], but no conclusions on possible non-uniformities of the composition inside the NWs can be drawn.…”
Section: Compositional Analysismentioning
confidence: 99%